Central pathology review of salivary gland adenoid cystic carcinoma. Issue 8 (23rd January 2020) - Ueda, Kaori; Murase, Takayuki; Nagao, Toshitaka; Kusafuka, Kimihide; Urano, Makoto; Yamamoto, Hidetaka; Nakaguro, Masato; Taguchi, Ken‐ichi; Masaki, Ayako; Hirai, Hideaki; Kawakita, Daisuke; Tsukahara, Kiyoaki; et al.
Abstract: Background: To assess the role of a central pathology review in the diagnosis of salivary gland adenoid cystic carcinoma (AdCC). Methods: Surgically resected salivary gland tumors diagnosed as AdCC (n = 219) in 15 reference hospitals in Japan were subjected to a retrospective pathological re‐evaluation. Results: After the review, the AdCC diagnosis was revised in 21/219 cases (9.6%). The six benign tumors (2.7%) comprised five basal cell adenomas and one pleomorphic adenoma, and among these six patients, three received postoperative radiotherapy. The remaining 15 malignant tumors (6.8%) comprised nine basal cell adenocarcinomas and six other carcinomas. All revised basal cell adenoma/adenocarcinoma cases were of rare cribriform variants. Conclusions: A significant proportion of AdCC pathology reports were revised after the central pathology review. It should be emphasized that the greatest attention should be paid in differentiating AdCC from cribriform variant basal cell adenoma/adenocarcinoma, which is very rare in salivary gland tumors.